Vers I'ALETA? Le libre-échange transatlantique et la politique étrangère canadienne - Wolfe, Robert (Études internationales, 1996)
This paper begins by reviewing some of the theoretical issues to be canvassed in any consideration of trade and foreign policy. The empirical core of the paper is a description of the many recent proposals to enhance transatlantic relations, it then turns to consideration of a puzzle : why has this resurgence of Atlanticist fever in trade policy happened now ? Finally, in the conclusion, it discusses whether the Transatlantic Free Trade Area (TAFIA) is meant to be an objective of policy in its own right, or an instrument used in pursuit of some other objective. The paper concludes that TAFTA is not significant for trade policy, but it is for foreign policy.